Activities of the wintering party party of the 27th Japanese Antarctic Research Expedition in 1986-1987 - Yasuhiko Naito (National Institute of Polar Research, 1988)
The wintering party of the 27th Japanese Antarctic Research Expedition composed of 35 personnel carried out routine and research observations of more than fifty items at Syowa Station, Mizuho Station and Asuka Camp, along the coast of Lutzow-Holm Bay and the Prince Olav Coast for a period between February 1986 and January 1987. Among three major research programs such as monitoring study of the upper atmospheric phenomena at Syowa Station, glaciological study in the East Queen Maud Land area, medical and biological study at Syowa Station and in the coastal area of Lutzow-Holm Bay and Prince Olav Coast, special efforts were made on the glaciological survey. The traverse party was sent out from Syowa Station to Asuka Camp in order to conduct the JMR observation that enabled precise measurements of the ice sheet movement. Along the traverse routes, ice core drilling, ice radar observation, meteorite survey and others were also conducted. An airborn ice radar survey was also carried out in the East Queen Maud Land area. Among other observations at Syowa Station, multibeam riometer observation was carried out to measure cosmic noise absorption. Ozone, CO_2,and other minor constituents in the atmosphere were studied by a variety of methods. Along the coastal area of Lutzow-Holm Bay and Prince Olav Coast, 51 ice-free localities were visited to study biology of lichen.